2022
DOI: 10.3390/brainsci12081041
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Allergic Asthma Induces Prenatal Neuroinflammation

Abstract: Autism spectrum disorder (ASD) is a class of neurodevelopmental disorders characterized by impaired social interactions and communication skills and repetitive or stereotyped behaviors. Rates of ASD diagnosis continue to rise, with current estimates at 1 in 44 children in the US (Maenner 2021). Epidemiological studies have suggested a link between maternal allergic asthma and an increased likelihood of having a child diagnosed with ASD. However, a lack of robust laboratory models prevents mechanistic research … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 58 publications
0
26
0
Order By: Relevance
“…All of the anatomical and endocrine outcomes were from a sheep model of HDM-induced maternal asthma, including placental weight [ 33 , 67 ], placentome maturity [ 33 , 68 ] and the isoforms and subcellular localisation of glucocorticoid [ 67 ] and androgen receptor isoforms [ 67 , 69 ]. The immune outcomes were from two mouse studies that measured cytokine production by placental lymphocytes [ 56 , 70 ].…”
Section: Resultsmentioning
confidence: 99%
“…All of the anatomical and endocrine outcomes were from a sheep model of HDM-induced maternal asthma, including placental weight [ 33 , 67 ], placentome maturity [ 33 , 68 ] and the isoforms and subcellular localisation of glucocorticoid [ 67 ] and androgen receptor isoforms [ 67 , 69 ]. The immune outcomes were from two mouse studies that measured cytokine production by placental lymphocytes [ 56 , 70 ].…”
Section: Resultsmentioning
confidence: 99%
“…A recent study described that the IFN-γ level was increased in the ASD brain [ 65 ]. It has been shown that IFN-γ level is elevated in children with ASD [ 9 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further, we used maternal marital status (together with maternal educational level) as a proxy for socioeconomic status, as we do not have more nuanced measures of socioeconomic status in this cohort. The parent cohort was designed to be enriched for asthma and allergies [ 45 ], which may themselves associate with child neurodevelopment and limit the generalizability of these findings to other populations [ 46 ]. We did not have information on time of day of blood collection, proinflammatory cytokines do exhibit a circadian rhythm [ 47 ], but we were unable to account for this in our analyses which may have influenced our findings.…”
Section: Discussionmentioning
confidence: 99%